Balancing fun and professionalism in game development: the dark and light side of play in virtual meetings - Bouzek, Dalton; Foxman, Maxwell; Lim, Chaeyun; Leith, Alex P. (Frontiers in Communication, 2025)
IntroductionThe COVID-19 pandemic accelerated remote work adoption in the game development industry, an already precarious field characterized by “crunch” culture and ludopolitics. Against this backdrop, this study examines the dual nature of “play” in virtual meetings (VMs) among game industry professionals (N = 38).MethodsThrough semi-structured interviews, we identify three primary manifestations of play: self-presentation through avatars and backgrounds, technological experimentation, and direct gameplay.ResultsOur findings reveal that playful elements simultaneously offer benefits, or “light” sides—enhanced creativity, reduced video conferencing fatigue, improved team cohesion and drawbacks, or “dark” sides—distractions, reduced professionalism in client-facing settings.DiscussionContext emerges as a critical determinant of play’s appropriateness—indie studios embrace playfulness more readily than corporate environments, while brainstorming sessions accommodate play better than task-oriented meetings. Avatar use particularly highlights this complexity, potentially reducing fatigue while raising concerns about professional trust. These findings contribute to understanding how game developers navigate integrating play into professional spaces, suggesting that successful implementation requires careful consideration of meeting context, company culture, and workplace objectives.